1984
DOI: 10.1152/jappl.1984.57.6.1632
|View full text |Cite
|
Sign up to set email alerts
|

Surrounding structures affect pressure-diameter behavior of excised dog bronchi

Abstract: The effects of adjacent large blood vessels, fibroelastic membrane, and parenchyma on pressure-diameter (P-D) behavior of intrapulmonary bronchi were studied in five dog lung lobes. Central lobar airways were inflated separately by blocking all branches with beads and inflating the distal lobar air spaces via pleural capsules. After bronchial P-D curves were obtained at fixed pleural pressures (Ppl) of -30, -10, and -5 cmH2O, the P-D properties of the isolated bronchi were measured in each of four stages of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Dynamic distention of the airways is limited by bronchomotor tone and by the passive properties of the airway wall and the surrounding parenchymal structures (28,29). During early development bronchomotor tone is decreased and the lung parenchyma is relatively underdeveloped.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic distention of the airways is limited by bronchomotor tone and by the passive properties of the airway wall and the surrounding parenchymal structures (28,29). During early development bronchomotor tone is decreased and the lung parenchyma is relatively underdeveloped.…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of peribronchial pressure has been investigated in various studies and has been found to approximate lung recoil pressure. Nakamura et al (16,17) deduced that in intact lobes, peak peribronchial parenchymal stress averaged Ϫ29 cmH 2 O at total lung capacity. Because bronchial transmural pressure of intraparenchymal airways is determined by peribronchial interstitial pressure, the loss of parenchymal attachments would have a significant effect on bronchial cross section during forced deflation.…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, the visceral pleura is reflected from the parenchyma onto the lobar bronchi, and this reflection extends upward onto the central airways. It has been shown that a negative interstitial or peribronchial pressure develops between the parenchyma and the lobar bronchus, and this negative interstitial pressure is determined by the degree of parenchymal inflation (16,17,20,21,23). When lobes are removed, it is possible that peribronchial pressure (i.e., pressure between reflected pleura and central airways) may also become less negative during the forced expiratory maneuver compared with the intact lung.…”
mentioning
confidence: 99%